Nuclear policy of Iran and international community (Journal of Oriental Studies, 2017)
The article gives an analysis of Iran’s nuclear program in the contextof relations with the international community. Iran’s cooperation with internationalorganizations according to its nuclear policyhas a great importance,especially in the light of the lifting of the latest political sanctionsof Europe and the US directed against Iran’s nuclear program. There aremany contradictions between the United States and Iran as «virtual nuclearstate»,developing nuclear technologies, as well as the enrichment ofuranium for peaceful purposes. The interaction of Iran with internationalcommunities, in which both sides are interested, alleviates these contradictionsand promotes closer cooperation and compromises in their furthercooperation.